2021
DOI: 10.21203/rs.3.rs-909940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Musculoskeletal Medicine Knowledge Among Physicians and Physical Therapists in Saudi Arabia: A Cross-Sectional Study

Abstract: Background: Musculoskeletal (MSK) conditions are rapidly rising in Saudi Arabia and considered the 3rd reason for hospital visits across the country. Despite their prevalence, the adequacy of knowledge in MSK medicine has not been assessed. The purpose of this study is to assess MSK medicine knowledge amongst healthcare providers (orthopedists, primary care physicians, and physical therapists) and medical and physical therapy students and interns.Method: In this cross-sectional study, a web-based 25-question M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…A study conducted at Harvard Medical School during the 2005-2006 academic year demonstrated that students had poor cognitive mastery, low clinical confidence, and were dissatisfied with the time devoted to musculoskeletal education (7). A cross-sectional study that evaluated knowledge of musculoskeletal medicine among physicians and physical therapists in Saudi Arabia showed that there is inadequate knowledge of musculoskeletal medicine among primary care physicians and physical therapists (8). A review of previous research on the competency in musculoskeletal education in medical schools showed that there is clear evidence that undergraduate medical programs do not adequately prepare future physicians in musculoskeletal medicine (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at Harvard Medical School during the 2005-2006 academic year demonstrated that students had poor cognitive mastery, low clinical confidence, and were dissatisfied with the time devoted to musculoskeletal education (7). A cross-sectional study that evaluated knowledge of musculoskeletal medicine among physicians and physical therapists in Saudi Arabia showed that there is inadequate knowledge of musculoskeletal medicine among primary care physicians and physical therapists (8). A review of previous research on the competency in musculoskeletal education in medical schools showed that there is clear evidence that undergraduate medical programs do not adequately prepare future physicians in musculoskeletal medicine (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%